Scanning Electron Microscopy of Glucose-Induced Cataract Treated with Garcinia mangostana Linn Pericarp Extract - Muhammad Ali Faisal; Ika Kustiyah Oktaviyanti; Hidayat Sujuti; Achmad Rudijanto (Fakultas Kedokteran Universitas Lambung Mangkurat, 2022)
Garcinia Mangostana Linn (GML) plant is one of the biodiversity of wetland area in South Kalimantan. GML pericarp contain various secondary metabolites, one of which is xanthones. Xanthones have antioxidant, antiinflammatory, reductase aldose inhibitor activity. This study aims to prove the potential of GML pericarp in the prevention of cataractogenesis by incubating the clear goat eye lens into a growth medium 199 for 120 hours in 5 groups. The positive control group which only given 30 mM glucose into the medium and the treatment groups that were given 30 mM glucose together with the mangosteen pericarp ethanol extract (EEKM) at a dose of 100, 500 and 1000 µg/ml. The results of scanning electron microscope (SEM) on the lens of the positive control group show irregularities of the cell arrangement of the lens fibers were evident. The lens fiber cells in the group given 100 µg/ml EEKM are still regularly arranged. In the group given 500 µg/ml EEKM, the lens fiber cells are still arranged regularly. In the group given 1000 µg/ml EEKM, the lens fiber cells are arranged regularly like the arrangement of fiber cells in the negative control group. This study proves that EEKM is able to prevent cataracts at least through the maintain the regularity of lens fibre cells and the clarity of the lenses. The drawback of this study is the use of crude extracts from EEKM so that it cannot be known specifically which active compounds are involved in the prevention of cataractogenesis. It can be concluded that the administration of EEKM at doses of 100, 500 and 1000 µg/ml can prevent cataracts and damage to the lens structure of the eye.